ประสิทธิภาพการทำงานของระบบติดตามตรวจสอบแบบออนไลน์ในโรงบำบัดน้ำเสียของโรงงานอุตสาหกรรม - ฉัตรไชย รัตนไชย (มหาวิทยาลัยสงขลานครินทร์, 2023)
The main objective of this study was to compare the measuring capacities of BOD/COD online analyzer with the standard methods used in laboratory. Meanwhile, to the measuring Spectrophotometry Analyzer and standard methods used in laboratory with the parameters analyzed in this study were BOD5, COD NO3-N and Suspended Solids (SS). The results showed that the online analyzer could not measure synthetic wastewaters which were not aerated, the error measuring of BOD5, and COD were over the acceptable ranges. The synthetic aerated wastewaters, concentrated between 0-100 0-200 and 0-100 mg/, gave error of 6.35 2.33 and 11.69 %, for BOD5 COD and SS, respectively. The Ministry of Industry Notice (2002) Issued Pursuant to Content Values of difference of BOD and COD not more than +15%. The results also showed that the reliable of measuring domestic wastewaters, effluent from palm oil industry and effluent from seafood industry were acceptabie. Ultraviolet absorbance could be used to estimate many parancters with different reliabities. Absorbance of 260 nm and 500 550 could be used for measuring COD and SS.